Perspektif Kewenangan Badan Pemeriksa Keuangan (BPK) Kaitan Perjanjian Eksteradisi Indonesia dan Singapore - Pandri Zulfikar (Jurnal Ilmiah Penegakan Hukum, 2022)
This article aims to find the relationship between the authority of the results of the Supreme Audit Agency's examination of the types of audits. Audits with a Specific Purpose are carried out as a follow-up to financial audits and audits because it is suspected that there is a criminal element in financial actions or the performance of agencies that have been examined, prosecuted and decided which have permanent legal force ( inkracht van gewijds) while the Convicted fled the country. The problem is how the duties and authorities of the State Audit Board are related to the Extradition Treaty of the Republic of Indonesia with the State of Singapore and what is the effectiveness of the Extradition Agreement of the Republic of Indonesia with the State of Singapore. The type of research used is qualitative with the type of normative research. Legal materials are analyzed qualitatively by explaining theories, logical principles to obtain scientific results that are descriptive. The results show that the Extradition Treaty of the Republic of Indonesia and the State of Singapore was signed by the Extradition Treaty of Indonesia and Singapore, aiming to prevent and eradicate transnational criminal acts, such as corruption. by the requesting State for prosecution or trial or execution of sentences for extraditable offenses